Genomic characterization and molecular docking identified a copper amine oxidase involved in Huperzine A biosynthesis in endophytis fungi Daldinia sp.TLC19 - Do, Thuy Phuong; Nguyen, Khac Hung; Le, Thi Minh Thanh; Pham, Thi Thoan; Pham, Bich Ngoc (Vietnam Journal of Biotechnology, 2025)
Huperzine A (HupA), a lycopodium alkaloid derived from several species of the Huperzia family and some filamentous fungi, has been studied intensively for decades due to its reversible inhibition of acetylcholinesterase and enhanced cognitive function. In our previous study, nine HupA producing endophytic fungi were isolated from Huperzia javanica, including high yield species Daldinia sp. TLC19 with a HupA concentration of approximately 0.305 mg/g dry cellular weight (dcw). In order to determine the essential genes involved in the HupA biosynthesis pathway in Daldinia sp. TLC19, the whole genome sequencing was performed. Reads were assembled following the Hierarchical Genome Assembly Process (HGAP) method. The genome size was 41 MB and the GC content was about 48.2%. BUSCO analysis revealed high-quality assembly with a completeness score of approximately 98.5% and the repetitive gene ratio of around 0.1%. A putative copper amine oxidase (CAO), which catalyzes the transformation of cadaverine to 5-aminopentanal in the HupA biosynthesis pathway, was determined based on genome annotation with GenBank, the protein domain database and protein secondary structure mapping. In the molecular docking analysis, the binding of cadaverine to topaquinone (autocatalytic oxidation of tyrosine residue 415) at the active site supported the determination of Daldinia sp. TLC19 copper amine oxidase. Our finding on the copper amine oxidase encoding gene of endophytic fungi TLC19 could be used in further research on high HupA producing strain improvement.